2018
DOI: 10.1093/intqhc/mzy079
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of diagnostic pathways for patients presenting with acute abdominal pain

Abstract: Pathways incorporating routine imaging will improve early diagnosis, but has not been proven to reduce complication rates or hospital length of stay. On the basis of this systematic review conclusions can therefore not be drawn about the pathways described and their benefit to the diagnostic process for patients presenting with abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…We found that children with a behavioral health diagnosis had a shorter time to PSG, perhaps reflecting greater physician or caregiver motivation to pursue diagnosis and treatment in these children. 36,37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that children with a behavioral health diagnosis had a shorter time to PSG, perhaps reflecting greater physician or caregiver motivation to pursue diagnosis and treatment in these children. 36,37…”
Section: Discussionmentioning
confidence: 99%
“…We found that children with a behavioral health diagnosis had a shorter time to PSG, perhaps reflecting greater physician or caregiver motivation to pursue diagnosis and treatment in these children. 36,37 When compared with White and Hispanic children, Black children more often had medical management recommended by the surgeon. Black children were also more likely to already use intranasal corticosteroids or leukotriene receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Hier wird nahezu einvernehmlich geraten, dass im Zweifel diese Untersuchung durchgeführt werden soll. Somit zeigt sich, wie in der vorliegenden Untersuchung auch festgestellt, ein Anstieg der vorgenommenen CT-Untersuchungen [9][10][11][12].…”
Section: Literaturvergleichunclassified
“…Острая боль в животе у детей (ОБЖД) представляет серьезную проблему для врачей как первичного звена, так и специализированных отделений. Она определяется как острая боль нетравматического происхождения, длительностью до 5-7 суток, требует качественной диагностики, быстрого лечения, в ряде случаев -срочного хирургического вмешательства [1,2,3,4].…”
Section: Introductionunclassified